2022
DOI: 10.1097/j.jcrs.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes of a new nondiffractive extended depth-of-focus intraocular lens targeted for minimonovision: 3-month results of a prospective cohort study

Abstract: To evaluate visual outcomes, spectacle independence, and optical phenomena after bilateral implantation of a nondiffractive extended depth-of-focus (EDoF) intraocular lens (IOL) targeted for minimonovision.Setting: University Eye Clinic Maastricht, the Netherlands. Design:Prospective case series. Methods: Patients with age-related cataract were bilaterally implanted with a nondiffractive EDoF IOL (Alcon AcrySof IQ Vivity), targeted for minimonovision. Outcome measures were the uncorrected distance visual acuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 25 publications
6
34
1
1
Order By: Relevance
“…Arrigo et al reported on the refractive outcome; far, intermediate, and near vision and quality of vision score in 54 healthy patients [ 9 ]. Gundersen and Potvin studied the effects on the binocular defocus curve in 40 healthy patients by simulating myopia in the nondominant eye [ 8 ] and a group from the Netherlands reported the refractive outcomes, defocus curves, spectacle independence, photic phenomena, and Catquest-9SF questionnaires in 22 healthy patients targeted for monovision [ 11 ]. Kohnen et al studied these same outcome measures in a group of 16 healthy patients targeted for emmetropia [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Arrigo et al reported on the refractive outcome; far, intermediate, and near vision and quality of vision score in 54 healthy patients [ 9 ]. Gundersen and Potvin studied the effects on the binocular defocus curve in 40 healthy patients by simulating myopia in the nondominant eye [ 8 ] and a group from the Netherlands reported the refractive outcomes, defocus curves, spectacle independence, photic phenomena, and Catquest-9SF questionnaires in 22 healthy patients targeted for monovision [ 11 ]. Kohnen et al studied these same outcome measures in a group of 16 healthy patients targeted for emmetropia [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kohnen et al reported a monocular UCDVA and CDVA of 0.12 ± 0.14 logMAR and 0.01 ± 0.05 logMAR, respectively [ 10 ], while the group from the Netherlands found a CDVA of −0.04 ± 0.11 logMAR in the dominant eye [ 11 ]. Arrigo et al reported a monocular UCDVA and CDVA of 0.1 ± 0.04 and 0.0 ± 0.03, respectively [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations